2013
DOI: 10.1109/jcn.2013.000104
|View full text |Cite
|
Sign up to set email alerts
|

Wireless communication at 310 GHz using GaAs high-electron-mobility transistors for detection

Abstract: We report on the first error-free terahertz (THz) wireless communication at 0.310 THz for data rates up to 8.2 Gbps using a 18-GHz-bandwidth GaAs/AlGaAs field-effect transistor as a detector. This result demonstrates that low-cost commercially-available plasma-wave transistors whose cutoff frequency is far below THz frequencies can be employed in THz communication. Wireless communication over 50 cm is presented at 1.4 Gbps using a unitravelling-carrier photodiode as a source. Transistor integration is detailed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…This has been shown by Blin et al [20,21] who was the first to use single FET detectors for THz wireless communication. In these experiments, GaAs HEMTs were wire bonded to a 50 Ω printed circuit board (PCB) based transmission line followed by laboratory wideband amplifiers.…”
Section: -P1mentioning
confidence: 73%
See 2 more Smart Citations
“…This has been shown by Blin et al [20,21] who was the first to use single FET detectors for THz wireless communication. In these experiments, GaAs HEMTs were wire bonded to a 50 Ω printed circuit board (PCB) based transmission line followed by laboratory wideband amplifiers.…”
Section: -P1mentioning
confidence: 73%
“…The FET detector can be modulated at high frequencies depending on the applied gate bias voltage and the used channel length [27]. As mentioned in Section 1, Blin et al [20,21] have demonstrated the potential of such applications by successfully detecting data rates up to 8.2 Gbps data using discrete GaAs transistors. However, this has not been yet demonstrated in an integrated solution.…”
Section: Fet Based Thz Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, unique THz electronic devices utilizing the plasma-wave effect in field-effect transistors [45]- [47] and the resonant tunneling effect [30], [33], [48], [49] have attracted much interest, because they can be operated as both transmitters and receivers.…”
Section: Transmitters and Receiversmentioning
confidence: 99%
“…They are considered as a good candidate for imaging, tomography, spectroscopy, as well as for future high data-rate THz wireless communications. [1][2][3][4][5][6] These applications require high speed and high responsivity detectors, integrated monolithically with antenna and readout electronics.…”
Section: Introductionmentioning
confidence: 99%